(untitled) (Eurasian Journal of Law, Finance and Applied Sciences, 2026)
This scientific study analyzes the legal foundations for extending the duration of pre-investigation checks in the criminal procedural legislation of the Republic of Uzbekistan, as well as current practical challenges. The research examines the content of Article 329 of the Criminal Procedure Code, along with normative legal acts related to the timeframes of forensic examinations, audits, and other complex investigative actions.